Introduction. Dissent, Disorder and Resistance: The Bourbon Restoration in Spain and its discontents (1875-1898) - Higueras Castañeda, Eduardo (Hispania Nova, 2025)
Order, stability and consensus are characteristics that part of the historiography has attributed to the political regime of the Restoration as opposed to the chaos and social polarisation that, according to the same account, predominated in the immediately preceding period. The commemoration of the 150th anniversary of the Revolution of 1868 and the First Republic, however, has served to revise this period and rethink it as a time of intense politicisation in a democratic sense, so that the coup d’état of General Martínez Campos must be read within a dynamic of de-democratisation confronted by different protest and resistance movements. This dossier focuses on both the internal ruptures and the rearticulation that the main opposition movements to the Canovist regime underwent from the years immediately after the return of the Bourbons to the throne until the consolidation of the system. In this sense, priority has been given to the introduction of new perspectives that contribute to the renewal of the debates on the Restoration in the context of its 150th anniversary.